2020
DOI: 10.1021/acscentsci.0c00133
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Visualization for Early-Stage Evolution of Polymer Aging

Abstract: Monitoring the evolution of polymer aging, especially early-stage aging, over both time and dimensionality can provide in-depth insight into aging-induced material invalidation and even disastrous accidents. However, it remains a great challenge because currently available methods for polymer aging only provide statistic results at a macroscopic scale. Herein, we report the first three-dimensional early-stage visualization (ESV) technique of polymer aging by using the fluorophore-bonded boronic acid to specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The fluorescence intensity of CD/SiO 2 particles in the stretched polypropylene film can be quantified as a gray value using Leica Application Suite X software (Figure S11). , As expected, the fluorescence intensity of the CD/SiO 2 particles was also positively correlated with stress. When the stress reached 8.2 MPa, the fluorescence intensity of CD/SiO 2 particles was 5.5 times higher than that in the absence of stress and 1.8 times higher than that of fluorescent CDs (Figure d).…”
Section: Results and Discussionsupporting
confidence: 82%
“…The fluorescence intensity of CD/SiO 2 particles in the stretched polypropylene film can be quantified as a gray value using Leica Application Suite X software (Figure S11). , As expected, the fluorescence intensity of the CD/SiO 2 particles was also positively correlated with stress. When the stress reached 8.2 MPa, the fluorescence intensity of CD/SiO 2 particles was 5.5 times higher than that in the absence of stress and 1.8 times higher than that of fluorescent CDs (Figure d).…”
Section: Results and Discussionsupporting
confidence: 82%
“…These LDH particles exhibited platelike morphology with the size distributed around 1 μm (Figure S2C). It has been reported that the boric acid group could target hydroxyl groups in the organic sugars or polyol compounds to form a cyclic boronic ester under mild environments. , To this end, 3-(10-phenyl-9-anthracenyl) phenyl boronic acid (DPBA), a blue emissive fluorescent molecule with boronic acid groups (Figure S3), was employed to target the hydroxide groups on the surface of LDHs through the specific B–O reaction. The labeled LDH particles showed the typical fluorescence emission as DPBA molecules (Figure A).…”
Section: Resultsmentioning
confidence: 87%
“…Selective etching or infiltration methods can be used to enhance contrast, but these can lead to potential sample damage and an inability to study dynamics in situ . As a comparison, fluorescence microscopy uniquely enables specific staining of the species of interest by means of chemistry or physical interactions or using a material’s intrinsic fluorescence emission. , …”
Section: Fluorescent Labeling For Imaging With Chemical Specificity A...mentioning
confidence: 99%
“…54 As a comparison, fluorescence microscopy uniquely enables specific staining of the species of interest by means of chemistry or physical interactions or using a material's intrinsic fluorescence emission. 55,56 Preferential solubility of staining agents into a particular polymer phase can be achieved by hydrogen bonding or other selective interactions. In seminal work, Hell et al were able to visualize the morphologies of block copolymer thin films using STED (Figure 2).…”
Section: ■ Breaking the Optical Diffraction Limitmentioning
confidence: 99%